The experience of using fesoterodine in patients with overactive bladder in the older age group - Elena I. Ermakova (IP Berlin A.V., 2020)
Aim. To evaluate the effectiveness and tolerability of the drug fezoterodin in older patients with оveractive bladder (OAB). Materials and methods. In 2019, 50 women with OAB aged 50 to 82 years (average age was 67.512.5 years) were treated in the framework of donation of the drug fezoterodin (Toviaz). The patients were divided into two groups: group 1 included 25 women had received treatment with fesoterodine dose of 4 mg per day for 12 weeks, group 2 consisted of 25 women, the fesoterodine dose to 8 mg per day for 12 weeks. The diagnosis of OAB was confirmed by a urodynamic study. Results. 48 (96%) patients out of 50 completed a 12 week course of treatment. The efficacy and tolerability of the drug fezoterodin in both groups was 93.7%. Mild adverse events (dry mouth, constipation, blurred vision) were observed in 11 (22.9%) patients out of 48 treated. None of the women had cognitive impairment (memory impairment, decreased concentration, drowsiness, impaired thinking and orientation). Conclusion. Our experience with M-cholinoblocator fezoterodin showed statistically and clinically significant improvements in all symptoms of OAB, as well as good tolerability of the drug in patients aged 50 to 82 years.